الحوكمة العالـمية والسلطة الخاصة: دروسٌ منسيةٌ في حوكمة الصحة العالـمية زمنَ جائحة كورونا - خير شهرزاد; حمشي محمد (المجلة الجزائرية للأمن والتنمية Algerian Review of Security and Developement, 2021)
تناقش هذه الدراسة إشكالية العلاقة بين السلطة الخاصة والحوكمة العالمية، وهي تسعى للاشتباك مع مفهوميْ السلطة والسلطة الخاصة، وتلفت الانتباهَ إلى الحاجةِ للمزيد من التأمل في أنماطها التي ما فتئت تتطور مع نمو الفواعل غير الدول وتعقد أدوارها في السياسة العالمية. كما تناقش التحول من الحوكمة العامة إلى الحوكمة الخاصة، وتحاجّ بأن هذا التحول إنما يرتبط بما يعرف بالمؤسسات الخاصة التي تنشأ عن تعزيز التعاون بين الفواعل الخاصة، بمختلف أشكالها وأدوارها ومجالات تأثيرها في عمليات الحوكمة العالمية. من ناحيةٍ أخرى، تسعى الدراسة إلى استنباط بعض الدروس لحوكمة الصحة العالمية التي سرعان ما طواها النسيان مع تفشي جائحة كورونا وما رافقها من عودةٍ للسياسة المتمركزة حول الدولة. This study debates the private authority and global governance nexus; it seeks to engage the concepts of authority and private authority and draws attention to the need for more reflection on the types of private authority that have been developing with the growth of nonstate actors and the complexity of their roles in global politics. Furthermore, it debates the shift from public to private governance, and argues that such a shift relates to private institutions arising constantly from strengthening cooperation among private actors, in their various forms, roles and areas of influence within global governance processes. Moreover, the study attempts to draw some lessons for global health governance; lessons that have been quickly forgotten with the outbreak of the Coronavirus pandemic and the return to state-centered politics.